Effect of Maleic Acid and Glycerol Concentrations on the Characteristics of Glycerol Ester of Maleic Rosin - Lukmandaru, Ganis; Sunarta, Sigit; Widiyatno, Widiyatno; Ramadhani, Rafli Nur (Masyarakat Peneliti Kayu Indonesia, 2024)
Gum rosin, distilled from the resin of pine trees (Pinus merkusii), is highly susceptible to degradation and oxidation. To maintain its quality, modification by fortification, among other methods, should be made, where a stable product named glycerol ester of maleic rosin (GEMR) is produced. In the experiment reported in this paper, rosin was prepared on the laboratory scale. Fortification was performed using maleic acid of varied concentrations (8%, 10%, and 12%, w/w), followed by mixing with glycerol through an esterification process (10%, 12%, and 14%, w/w). The average yield of GEMR produced was in the range from 67.11% to 79.30%. The average softening point, acid number, and ash content were in the ranges of 91.67–120.67°C, 5.84–9.82 mg KOH/g, and 5 x 10-3–14.7 x 10-3%, respectively. No significant effect of concentration was observed on yield and acid number. The GEMR product was completely soluble in toluene at all concentration levels. It was found that the increase of glycerol portion affected the properties of GEMR, i.e., lower ash content and acid number, while higher softening point. Based on the acid number, solubility in toluene, and softening point values, the GEMR obtained in this research fulfilled the requirements of Chinese GEMR standards.